2020
DOI: 10.1007/s11657-020-00814-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of increased serum 25(OH)D and calcium on structure and function of post-menopausal women: a pilot study

Abstract: Summary The purpose was to determine if increasing serum 25(OH)D and calcium in postmenopausal women increased skeletal muscle size, strength, balance, and functional task performance while decreasing muscle fatigue. PCSA of the vastus lateralis increased and ascent of stairs time decreased after 6 months of increased serum 25(OH)D. Purpose The Institute of Medicine recommends ≥ 20 ng/ml of serum 25-hydroxyvitamin D [25(OH)D] for bone and overall health. Serum 25(OH)D levels have been associated with physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…showed that the daily intake of calcium- and vitamin D-rich milk in healthy postmenopausal women significantly improved vitamin D status, increased femoral neck BMD, and had favorable effects on glucose and lipid profiles ( 22 ). Studies have also confirmed that increased serum 25 (OH) D and calcium levels in postmenopausal women can increase skeletal muscle size, strength, balance, and functional task performance while reducing muscle fatigue ( 23 ). Furthermore, collagen peptide supplementation enhances the positive effect of calcium and vitamin D supplementation on bone metabolism in postmenopausal women ( 24 ).…”
Section: Discussionmentioning
confidence: 93%
“…showed that the daily intake of calcium- and vitamin D-rich milk in healthy postmenopausal women significantly improved vitamin D status, increased femoral neck BMD, and had favorable effects on glucose and lipid profiles ( 22 ). Studies have also confirmed that increased serum 25 (OH) D and calcium levels in postmenopausal women can increase skeletal muscle size, strength, balance, and functional task performance while reducing muscle fatigue ( 23 ). Furthermore, collagen peptide supplementation enhances the positive effect of calcium and vitamin D supplementation on bone metabolism in postmenopausal women ( 24 ).…”
Section: Discussionmentioning
confidence: 93%
“…al [5] studied vitamin D deficiency among north Indian athletes and considered the serum level <20 ng/ml as deficient, serum level 20-30 as insufficient, serum level >30 ng/ml as sufficient. Sinkar et.al [6] studied vitamin D deficiency picture considering 1079 Asian Indians from Indian laboratories considering clinical range <20 ng/ml as deficient, 21-30 ng/ml as insufficient, >30ng/ml as sufficient. They studied age-wise as well as gender-wise deficiency and considered the age groups 0-10, 10-25, 25-50 and age above 50.…”
Section: Introductionmentioning
confidence: 99%